Growth and biofilm formation of Cupriavidus metallidurans CH34 on different metallic and polymeric materials used in spaceflight applications. Issue 6 (3rd July 2022) - Abdeljelil, Nissem; Ben Miloud Yahia, Najla; Landoulsi, Ahmed; Chatti, Abdelwaheb; Wattiez, Ruddy; Van Houdt, Rob; Gillan, David
Abstract: Bacteria biofilm formation and its complications are of special concern in isolated structures, such as offshore stations, manned submarines and space habitats, as maintenance and technical support are poorly accessible due to costs and/or logistical challenges. In addition, considering that future exploration missions are planned to adventure farther and longer in space, unlocking biofilm formation mechanisms and developing new antifouling solutions are key goals in order to ensure spacecraft's efficiency, crew's safety and mission success. In this work, we explored the interactions between Cupriavidus metallidurans, a prevalently identified contaminant onboard the International Space Station, and aerospace grade materials such as the titanium alloy TiAl6V4, the stainless steel AISI 316 (SS316) and Polytetrafluoroethylene (PTFE) or Teflon. Borosilicate glass was used as a control and all surfaces were investigated at two different pH values (5.0 and 7.0). Biofilms were almost absent on stainless steel and the titanium alloy contrary to Teflon and glass that were covered by an extensive biofilm formed via monolayers of scattered matrix-free cells and complex multilayered clusters or communities. Filamentous extracellular DNA structures were observed specifically in the complex multilayered clusters adherent to Teflon, indicating that the employed attachment machinery might depend on the physicochemical characteristics of the surface.